Dongshaea marina gen. nov., sp. nov., a facultatively anaerobic marine bacterium that ferments glucose with gas production. Issue 11 (13th November 2018) - Huang, Ssu-Po; Chen, Tzu-Yin; Chen, Jwo-Sheng; Wang, Li-Ting; Huang, Lina; Lin, Shih-Ting; Wei, Chih-Lin; Lin, Saulwood; Wang, Pei-Ling; Chen, Yi-Min; Shieh, Wung Yang
Abstract : Two isolates of heterotrophic, facultatively anaerobic, marine bacteria, designated DM1 and DM2 T, were recovered from a lagoon sediment sample of Dongsha Island, Taiwan. Cells were Gram-reaction-negative rods. Nearly all of the cells were non-motile and non-flagellated during the late exponential to early stationary phase of growth, while a few of the cells exhibited motility with monotrichous flagellation. The two isolates required NaCl for growth and grew optimally at about 30 °C, 2–3 % NaCl and pH 7–8. They grew aerobically and could achieve anaerobic growth by fermenting d -glucose or other carbohydrates with production of acids and the gases, including CO2 and H2 . Ubiquinone Q-8 was the only respiratory quinone. Cellular fatty acids were predominated by C16 : 0, C18 : 1 ω7 c and C16 : 1 ω7 c . The major polar lipid was phosphatidylethanolamine. Strains DM1 and DM2 T had DNA G+C contents of 52.0 and 51.8 mol%, respectively, as determined by HPLC analysis. Phylogenetic analyses based on 16S rRNA gene sequences clearly indicated that the two isolates formed a distinct genus-level lineage in the family Aeromonadaceae of the class Gammaproteobacteria and was an outgroup with respect to a stable supragenic clade comprising species of the genera Oceanimonas, Oceanisphaera and Zobellella . The phylogenetic data and those from chemotaxonomic, physiological and morphological characterizations support the establishment of a novel species and genus inside the family Aeromonadaceae, for which the name Dongshaea marina gen. nov., sp. nov. is proposed. The type strain is DM2 T (=BCRC 81069 T =JCM 32096 T ).